2009
DOI: 10.4995/rlyla.2009.740
|View full text |Cite
|
Sign up to set email alerts
|

Cultural Domains: Translation Problems

Abstract: Abstract:Much of the lexis of a language has a cultural referent and is thus specific to a speech community. The meaning of culturally marked words is often difficult to grasp without some cultural knowledge and poses translation problems, particularly when the words are associated with cultural domains (Nida, 2001). In the present paper we focus on the French cultural domain of cooking. After outlining the elements of the domain, we analyse the difficulties in translating the lexical units from the domain and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 4 publications
0
7
0
Order By: Relevance
“…The analysis of the data views the participants' performance in translating these idioms used by Jordanian Arabic Southern Bedouin Area. Different criteria were used as the followings based on (Alousque 2009 literal translation which relates to conveying the meaning of the idiom from the source language into the target language in terms of word-for-word translation without referring to the sense of idiom in the source language. ii)…”
Section: Discussion and Findingsmentioning
confidence: 99%
See 2 more Smart Citations
“…The analysis of the data views the participants' performance in translating these idioms used by Jordanian Arabic Southern Bedouin Area. Different criteria were used as the followings based on (Alousque 2009 literal translation which relates to conveying the meaning of the idiom from the source language into the target language in terms of word-for-word translation without referring to the sense of idiom in the source language. ii)…”
Section: Discussion and Findingsmentioning
confidence: 99%
“…Style is considered as combination of different aspect of a language such as culture, costumes, heritage, semantic, pragmatic, ect. Alousque (2009) figures out cultural words which require a cultural background to be correctly recognized and thus indicating translation problems. The problems that face translators are cultural problems results because the cultural differences and their ignorance of the culture of the target language and dialects.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite its value to EFL students, translation as a process has many difficulties, including assessment (Dreyer & Marcu, 2012;Munday, 2012;Sireci et al, 2006), cultural (Alousque, 2010;Pshenitsyn, 2011;Sheorey, 2012), curriculum design (Avval, 2013;Bicer, 2003 ;Razmjou, 2001), linguistic (Pshenitsyn, 2011;Remish, 2012;Sheorey, 2012;Solomatina, 2018), or pedagogical (Bingbing, 2011;He, 2012;Heping, 2011;Hongmei, 2010;Josipović, 2017;Nazari & Ghasemi, 2016;Yan, 2012;Zainudin & Awal, 2012). Many questions have arisen as a result of these issues about how to lay the foundation to translation as a construct among EFL students.…”
Section: Review Of Literaturementioning
confidence: 99%
“…The study revealed a poor skills level of translating cultural expressions and wrong translation strategies by the students as most of them tended to give a literal translation of the phrases rather than giving any equivalent meaning. Alousque (2009) studied the challenges in translating cultural items with different semantic range both in the source and target languages and the range of translation procedures used to explain their meaning through the analysis of the lexis from the French cultural domain of cooking. He concluded that there are some difficulties of translating those cultural lexis.…”
mentioning
confidence: 99%